Emotion: the 'e' in engagement in online distance education in social work - Sophie Jennifer Goldingay (Flexible Learning Association of New Zealand, 2014)
Many social work students approach the pre-practicum practice skills unit with dread, due to the required role-play exercises designed to prepare them for practicum.  Online distance students may be seen to be challenged even further in their preparation for practicum due to a perception that they are learning practice skills on their own. A survey of online distance education social work students who had completed the practice skills course in 2012 showed that a number struggled to remain engaged and felt isolated.  A large percentage did not engage in all the set tasks, which may have contributed to them feeling unprepared for their first practicum experience. A pedagogy involving extensive online peer interaction linked to formative assessment of role plays was implemented for a subsequent cohort in the practice skills unit, with the aim of improving online distance students' opportunity and motivation to practice the required skills prior to their practicum. Learning platform usage data for students in the 2013 cohort showed that the number of times students accessed online readings and used interactive technology increased. Interestingly, while both cohorts expressed a positive emotional experience in relation to their learning in the end of trimester Student Evaluation Survey, only the 2013 cohort spontaneously articulated the content of what they actually learnt despite both groups being asked the same questions.  This suggests that the ongoing peer interaction generated by the intervention resulted in a deeper and enduring learning experience. In addition, students in the 2013 cohort demonstrated a feeling of being connected with the unit and the teaching staff. It is posited that a combination of reduced isolation and alienation, and ongoing peer feedback and self-reflection, has a multipronged positive impact on the process of learning, including a positive emotional experience as well as a developing sense of pride in one's professional identity and competence.